Switching the enzymatic activity of ribonuclease a based on enzyme/polymer complex formation - Ganguli, Sumon (Journal of Bio-Science, 2014)
Context: Enzymes are ideal for various applications in both medicine and biotechnology. Switching on/off the enzymatic activity of enzymes by polymeric modification would expand the applications of enzymes in a wide range of research fields. Objectives: On/off switching the enzymatic activity of RNase A and the confirmation of the enzyme/polymer complex formation which leads to improve the heat resistance of RNase A. Materials and Methods: ?-Methoxy-?-methacryloyl poly (ethylene glycol) (PEG-MA) macromonomer and PEAMA-g-PEG were synthesized. Bovine RNase A, cytidine 2?,3?-cyclic monophosphate sodium salt (cCMP), and 3-(N-morpholino)propanesulfonic acid (MOPS) were obtained from Sigma Chemical Co. (St. Louis, USA). PAAc (Mn = 5,000 g/mol) were purchased from Wako (Osaka, Japan). Sodium dihydrogen phosphate dihydrate (NaH2PO4.2H2O) was obtained from Nacalai Tesque Inc. (Kyoto, Japan). The enzymatic activity of RNase A was estimated as follows. The RNase A concentration was determined by measuring the absorbance at 280 nm with an appropritate blank, using an extinction coefficient of 7.10 mL mg-1 cm-1. A total of 1.5 mL of 0.1 mg/mL cCMP solution prepared in 0.1 M MOPS (pH 7.0) was mixed with 10 ?L of the RNase A solution in 50 mM sodium phosphate buffer (pH 7.0). The increase in light scattering intensity of the solution was monitored by measuring the absorbance at 284 nm for 60 s in a UV-vis spectrophotometer at room temperature. After heat treatment, the enzymatic activities were measured. Far-UV and near-UV CD spectra were monitored using a spectropolarimeter (model J-720W; Jasco, Tokyo, Japan). Results: We have found that poly (acrylic acid) (PAAc) suppressed the enzymatic activity of RNase A completely and the recovery of enzymatic activity were observed (94%) by the external addition of PEAMA-g-PEG to the RNase A/PAAc complex. Our present findings suggest that the complexation between PEAMA-g-PEG and RNase A has occurred which improve the heat resistance (64%) of RNase A. Heat treatment has been carried out at 98°C for 10 minutes where the native RNase A lost all of its enzymatic activity. CD spectral analysis also indicates that the conformation of the enzyme was not altered due to the complexation. Conclusion: Poly (N,N-diethylaminoethyl methacrylate)-graft-poly (ethylene glycol) (PEAMA-g-PEG) restored the enzymatic activity of RNase A completely which was inactivated upon the addition of poly(acrylic acid) (PAAc) to RNase A. Complexation of RNase A with PEAMA-g-PEG induced the improvement of heat resistance of RNase A . Circular dichroism (CD) spectral analysis clearly indicated that the complexation of enzyme with polymer has almost no influence on the conformation of enzyme. DOI: http://dx.doi.org/10.3329/jbs.v20i0.17650 J. bio-sci. 20: 33-39, 2012